2022
DOI: 10.21037/tp-22-260
|View full text |Cite
|
Sign up to set email alerts
|

Retraction: efficacy and safety of mineral trioxide aggregate (MTA) pulpotomy for caries-exposed permanent teeth in children: a systematic review and meta-analysis

Abstract: Recently, we found that some of the included articles were unqualified in our article entitled "Efficacy and safety of mineral trioxide aggregate (MTA) pulpotomy for caries-exposed permanent teeth in children: a systematic review and meta-analysis" (1) published in Vol 11, No 4 (April 2022) issue of Translational Pediatrics (TP). In order to correct this serious mistake, after discussion, we request that this article be retracted. We sincerely apologize to readers and the editors of the journal for any inconve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…At 1-year follow up, the success rate of MTA was 99.24%, significantly higher than the 94.53% of root canal treatment. The use of MTA as a pulp capping agent in pulpotomy for primary molars can effectively maintain the surgical effect, and the long-term efficacy was more ideal, consistent with the study of Wang et al [22]. Also, the study of Zhang et al [15] showed that in the root canal treatment group, the main reasons for failure were root bifurcation, root resorption, and pulp plate fracture.…”
Section: Discussionsupporting
confidence: 76%
“…At 1-year follow up, the success rate of MTA was 99.24%, significantly higher than the 94.53% of root canal treatment. The use of MTA as a pulp capping agent in pulpotomy for primary molars can effectively maintain the surgical effect, and the long-term efficacy was more ideal, consistent with the study of Wang et al [22]. Also, the study of Zhang et al [15] showed that in the root canal treatment group, the main reasons for failure were root bifurcation, root resorption, and pulp plate fracture.…”
Section: Discussionsupporting
confidence: 76%